Nematocyst types and venom effects of Aurelia aurita and Velella velella from the Mediterranean Sea. (February 2020) - Killi, Nurçin; Bonello, Guido; Mariottini, Gian Luigi; Pardini, Patrizia; Pozzolini, Marina; Cengiz, Sibel
Abstract: Natural substances produced by venomous marine organisms are thought to be possible sources of useful compounds and new drugs having the potential to open new ways for pharmacology, nutrition and environmental applications. In this framework, cnidarians are very interesting being widely distributed and all are venomous organisms; so, a deep knowledge of their occurrence, morphology of venomous structures and of effects of venoms at cellular level is fundamental to evaluate the possible utilization of venomous compounds or extracts. In this research, the morphology and occurrence of nematocysts in two cnidarian species ( Aurelia aurita, Velella velella ), and the preliminary evaluation of the cytotoxicity of V. velella crude extract, of which cytotoxicity on cell cultures at present is unknown, were considered. The specimens were sampled in Güllük Bay, Southwestern coast of Turkey, and in the Gulf of Genova, Northwestern coast of Italy. Six nematocyst types (a-isorhiza, A-isorhiza, O-isorhiza, eurytele, polyspiras, birhopaloid) having different sizes, were observed in A. aurita, and two types (eurytele and stenotele) in V. velella . The crude extract from V. velella showed cytotoxic activity against cultured fibroblasts L929 at high doses, while inducing cell proliferation at low doses. The protein content in the extract increased remarkably after disruption of nematocysts. Graphical abstract: Image 1098 Highlights: The shape of some nematocyst types differs in A. aurita sampled in different zones. Nematocyst number-bell diameter relationship was not observed in A. aurita. Only eurytele and stenotele nematocyst types were observed in V. velella. High doses of V. velella crude venom caused decrease of survival in L929 cells. Low doses of V. velella crude venom had positive effects on L929 cells.